Suplementação de colina protegida em vacas da raça holandesa no período de transição - Ciola, Fernando Freire (2019)
Metabolic disorders, such as ketosis, have been increasingly common in high production dairy herds. To evaluate preventive measures, as well as to know the metabolic profile of the cows in the transition period and their relationship with the nutritional status, is of paramount importance. Thus, the aim was to determine the influence of protected choline supplementation on the serum concentration of ketone bodies and cholesterol, body score, live weight and 30 and 60 days postpartum milk yield in Holstein cows. The animals were evaluated during the transition period, which presents major metabolic disorders, shared in two treatments: cows with protected choline supplementation and cows with no protected choline supplementation. Primparous and multiparous cows were used in a 20 days period before calving, extending up to 20 days after calving. The weighing of the cows was performed with weighing tape, the body score assessed visually, following a classification from 1 up to 5. Milk yield was performed through electronic meters in the milking parlour and blood cholesterol concentration was measured in a commercial laboratory. The measurement of ketone bodies was done through test strips, associating subclinical ketosis. Protected choline supplementation did not alter BHBA concentrations between treatments, nor was there a significant difference in ECC, live weight and milk production. Supplemented animals presented lower serum cholesterol concentration.